Study the effect of polyphenols extracted from Iraqi grape seeds on glucose , MDA levels and GST activity in streptozotocin (STZ ) induced diabetic mice. - Baghdad Science Journal (مجلة بغداد للعلوم)
1-Objective:- Polyphenols are biochemical compounds with antioxidant activity against differences diseases related to Lipid peroxidation such as diabetes mellitus. Polyphenols distributed widely in medical plants, the aim of the study is to extract and analyze some polyphenolic compounds from grape seeds and examine their effects on (STZ) induced diabetic mice. 2-Methods:- In the present study , a group of polyphenols has been extracted from Iraqi grape seeds by ethanol and the extract has been analyzed by using High Performance Liquid Chromatography (HPLC) coupled to ultra violet (UV) detection. Five fractions were eluted from the column : procyanidin B1, gallic acid , quercetin , catechin and epicatechin. The detection was recorded at (280 nm). The reactive action of the above polyphenols on glucose, and malondialdehyde (MDA) levels and glutathione – S – transferase (GST) activity was tested in (30) streptozotocin (STZ) induced diabetic mice which treated with extracted grape seeds polyphenols to examine the antioxidant effect of these compounds . Grape seeds polyphenols action on the above parameters was determined before treatment and after (1 week), ( 2 weeks) and (3 weeks) of treatment with this reactive extract. 3-Results:- The data have shown that glucose levels were increased in (30) diabetic mice (after injection with streptozotocin) compared with control group (p